PENGARUH SUPERVISI KEPALA SEKOLAH TERHADAP KINERJA GURU BAHASA ARAB DI MADRASAH ALIYAH MUALLIMIN MUHAMMADIYAH CABANG MAKASSAR - Mustabsyira Mustabsyira (Al-Maraji' : Jurnal Pendidikan Bahasa Arab, 2019)
This study aims to determine 1) Supervision of school principals at Madrasah Aliyah Muallimim Muhammadiyah Makassar Branch, 2) Performance of Arabic teachers at Madrasah Aliyah Muallimim Muhammadiyah Makassar Branch, 3) The effect of principal supervision on the performance of Arabic teachers at Madrasah Aliyah Muallimim Muhammadiyah Makassar Branch.This research is a descriptive correlational study in which all the variables to be observed, then correlated between the independent variable and the dependent variable. Data collection methods are observation, interview, questionnaire and documentation.The results obtained data that: 1) Supervision of the principal at Madrasah Aliyah Muallimim Muhammadiyah Makassar Branch is in the high category. These results are consistent with the distribution of frequencies and percentages obtained in the field, which shows that the supervision of the principal at Madrasah Aliyah Muallimim Muhammadiyah Makassar branch is around 57.14%. 2) The performance of Arabic teachers at Madrasah Aliyah Muallimim Muhammadiyah Makassar Branch is in the high category. These results are consistent with the distribution of frequencies and percentages which indicate that the performance of Arabic teachers at Madrasah Aliyah Muallimim Muhammadiyah Makassar branch is around 51.43%. 3) Principal supervision has a significant effect on the performance of Arabic teachers at Madrasah Aliyah Muallimim Muhammadiyah Makassar Branch, which is indicated by a significance value of P 0.000 0.05.